THE RELATIONSHIP BETWEEN EMPLOYEES’ JOB STRESS AND JOB PERFORMANCE: A CASE STUDY AT PEJABAT RESIDEN BAHAGIAN SAMARAHAN, SARAWAK - Caesar DeAlwis; Juliza Salleh; Norlina Mohamed Noor; Aida Nabilah Abdul Rafil; NurFarraEzlynn Hafizon (Jurnal Penyelidikan Sains Sosial, 2020)
Job performance refers to an employee’s proficiency, performing well in achieving goals and behaviour involving deliberate acts that are harmful to the organization. Since the research objective is to investigate the relationship between factors of job stress and job performance among staff; thus, Pearson Product Moment Correlation is used. As this is a case study, employees at Pejabat Residen, BahagianSamarahan, Sarawak were selected. This study applied The Job Demands-Control (JDC) Model by Karasek, which focused on two categories; job demand and job control. Job demand embraces two constructs, which are workload and time pressure. Job control comprises of skill discretion and decision authority. A total of 100 questionnaires conveniently distributed, and 91 were returned and considered usable. Correlation analysis, independent t-test, and ANOVA used to analyse the data. The result shows that job demand, job control, workload, and time pressure had a significant relationship with job performance. It proves that when the employees had a sufficient amount of time and decision making empowerment with task-related skills, their job performance increase. This research would contribute to the body of knowledge surrounding the job stress field that would affect the employees’ job performance. Besides, the result of this study would also benefit the management of the organization, where it would assist them in helping their employees to reduce the issue of the stress. Lastly, it can help to create awareness among the employees about factors related to stress and benefit themselves to handle their tasks more efficiently.